(1203) economic growth and industrial development policy سياسة النمو الاقتصادي والتنمية الصناعية - roman, zoltan (معهد التخطيط القومى, 2020)
The high rate of economic growth is perhaps the most general economic-political objective common probably to all countries. It is evidently not the only objective it is often coupled with other economic and social aims competing with one another, like full employment.